Energy Conservation: Successes and Failures - Sawhill, John C.; Cotton, Richard (Washington, D.C.: The Brookings Institution, 1986)
The worldwide recession of the late 1970s and early 1980s clouded analytic conclusions about whether the reductions in oil use experienced in those years resulted from the general economic slowdown or from real increases in the efficient use of energy resources. This book presents seven essays that seek to answer these questions. The results indicate that significant increases in energy efficiency have occurred and that further increases can be expected as capital stock with a long lead time, such as factories, buildings, and durable goods is replaced.
Includes bibliographical references and index.
ne 18/04/2018
Loans
Keywords: Energy Conservation; Energy Policy; Public Utilities; Petroleum Industry and Trade